Disclosure of psychosocial stressors affecting diabetes care among uninsured young adults with Type 1 diabetes. Issue 9 (26th June 2013) - Pyatak, E. A.; Sequeira, P.; Peters, A. L.; Montoya, L.; Weigensberg, M. J.
Abstract Aims To determine the disclosure rates of psychosocial issues affecting routine diabetes care. Methods A total of 20 young adults were interviewed regarding the impact of psychosocial stressors on their diabetes care. The interviewer, endocrinologist and case manager reported the prevalence rates of psychosocial stressors. Disclosure rates were compared to determine the prevalence of psychosocial issues and the different patterns of disclosure. Results Participants reported a high number of psychosocial stressors, which were associated with poorer glycaemic control (r = 0.60, P = 0.005). Approximately half of all disclosed stressors (50.9%) were identified in routine care; other stressors were identified only through intensive case management and/or in‐depth interviews. Conclusions Identifying psychosocial stressors in routine care, and providing referrals to psychological or social services, is a significant unmet need and may improve glycaemic control among certain populations with diabetes. Systematic mechanisms of capturing this information, such as by screening surveys, should be considered.